Awareness and Current Therapeutics of Asthma. Issue 3 (4th September 2019) - Zainab, Rida; Akram, Muhammad; Daniyal, Muhammad; Riaz, Muhammad
Introduction: Asthma is a serious allergic disorder of the respiratory system. It affects about 300 million people worldwide. This has a great burden on medical treatment. Several medicines are available, but they have many serious side effects. Therefore, there is a need to search for a new therapeutic agent with no or minimal side effects while most economical for patients. In folk medicine, antiasthmatics herbal medicine has been used and showed potential therapeutic antiasthmatic efficacy due to the presence of potential bioactive compounds. Methods: Different databases were searched (ie, Embase, PubMed, CBM, AMED, and CINAHL). We have reviewed the published data of the last 20 years. We used MeSH terms "asthma" herbal treatment of asthma, allopathic treatment of asthma, and treatment strategies for asthma. The traditional medicine was compared with modern medicine and the same pharmacotherapies alone or with placebo. The methodology was evaluated by using the GRADE summary of Finding tables and Cochrane Risk of Bias Tool. Results: There have been some clear-cut indications toward the recognition of further molecular and cellular mechanisms of asthma. Most of them recommend a further target for treatment. The novel procedures, biologics, and pharmaceuticals are evaluated. Both allopathic and herbal treatments of asthma are effective. Due to none or lesser side effects, herbal medicines are safer than conventional medicine. Conclusion: The preliminary documentation of the plants discussed in the review show the presence of several secondary metabolites that are responsible for the management of asthma and its relevant complications. Further research studies are needed to identify the bioactive compounds from these plants that have potential efficacy to cure asthma, and clinically based studies are needed to search for a complete cure for this disease.